Memória e representação: reflexões para a organização do conhecimento - Da Silva Farias, Mona Cleide Quirino [UNESP]; Bizello, Maria Leandra [UNESP] (My University, 2016)
This paper discusses the concept of memory based on a sociocultural perspective for a possible analysis of it as an element of representation in Knowledge Organization. Memory, from a sociocultural perspective, involves the practices and experiences of individuals and groups that share experiences and carry common meanings and become that, the representation of knowledge with collective and hybrid characteristics. We aim to discuss some conceptions of memory for a further analysis of the issue of knowledge representation. We assume that the ways of organizing and representing knowledge imply symbolic elements whose purpose is the representation of memory, that is, a semiotic mediation evidenced in the way that individuals share a repertoire of signs. Within this scope, we consider memory at both its individual and collective dimensions, as a semiotic element of knowledge. Thus, the conception of memory can not be reduced just to the idea of remembering and forgetting, since the object of memory is the individual and collective practices that turn into the dynamic way in which groups seek to represent their cultural memory mediated by a given historical and sociocultural context.
Memory and representation: Reflections for Knowledge Organization
Keywords: Cultural memory; Knowledge organization; Memory; Semiotic mediation